Engku Mohammad Sjafe’i dan INS Kayutanam: Jejak Pemikiran Pendidikannya - ZED, MESTIKA (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
This essay provides a preliminary analysis of the Mohammad Syafe’i’s educational thought, placing it within the context of the larger social and intellectual history of Indonesian society during the colonial time and after. The idea behind the establishment of the INS – the school founded by Sjafei in 1920s – justified and idealized national education as the form of intellectual resistance against the Dutch colonial regime on the basis of historical precedence found in Western educational expansion. This study traces (i) how did Sjafei develop his own philosophy of education? (ii) how did he redefine knowledge, education, schooling, teaching and learning? (iii) how did he challenge and change traditional concepts of education and curriculum as content of the whole learning processes? (iv) what the ideas or practices of the Syafei’s school contribution are present in today’s teaching and learning? (v) what contributions from his achievements are useful to the Indonesian national education in developing the country’s philosophy of education? In answering these questions, this article eventually comes to conclusion that in one way or another, one could qualify him as a pioneer of modern Indonesian education. Kata Kunci: pemikiran pendidikan, filsafat pendidikan, pengetahuan, pendidikan, sekolah